TINJAUAN KONSTITUSIONAL KEWENANGAN MAHKAMAH KONSTITUSI DALAM MEMUTUS SENGKETA PILKADA - Rusli, Rusli (Katalogis, 2015)
This research aimed at knowing the basic authority of a Law Court Constitution in deciding regional leader election before the existence of Law Court Constitution authority decision number 97/PUU-XI/2013 and analyzing the authority of Law Court Constitution in deciding Regional Leader Election Lawsuit after the decision of Law Court Constitution number 97/PUU-XI/2013. This research was normative law research through ordinance, historical and conceptual approach. The result of the research concludes that: 1) the basic authority of a Law Court Constitution in deciding regional leader election before the existence of Law Court Constitution authority decision number 97/PUU-XI/2013 exists due to interpretation development of regional leader election that becomes a part of general election regime which is written in section 24C UUD NRI 1945, it explains that Law Court Constitution is authorized as to decide the lawsuit deriving from a general election. 2) The authority of Law Court Constitution in deciding Regional Leader Election Lawsuit result written in MK No 97/PUU-XI/2013 created in Undang-Undang No 8 Tahun 2015 is inconstutional or against the section 22E and section 24C UUD NRI 1945. This case derives from Â the interpretation of law court constitution which states that regional leader election is no longer a part of general election regime in accordance with the law in section 22E UUD NRI 1945. The regulation in section 22E points out that general election is administrated to elect delegation of citizen council (DPR), regional delegation (DPD), President - vice president and delegation of regional council (DPRD). On the other side, Law section 24C UUD NRI 1945 mentions about related law court constitution without mentioning that regional leader election Â is a part of authority given to law court constitution.